THE TEACHING OF SCIENCE IN A LIBERAL ARTS PROGRAM. - Graubard, Mark (Science Education, 1960)
The article focuses on the scope of teaching of science in a liberal arts program in the U.S. The requirement of algebra and natural science for students at state universities. The general course can logically invade the field of science history or the impact of science on social events. It discusses the basic phenomena and laws of physics, chemistry and geology. The full appreciation of the historical quest for science requires understanding of cultural anthropology.